8(3y-6)-(7y+8)=

Simple and best practice solution for 8(3y-6)-(7y+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3y-6)-(7y+8)= equation:


Simplifying
8(3y + -6) + -1(7y + 8) = 0

Reorder the terms:
8(-6 + 3y) + -1(7y + 8) = 0
(-6 * 8 + 3y * 8) + -1(7y + 8) = 0
(-48 + 24y) + -1(7y + 8) = 0

Reorder the terms:
-48 + 24y + -1(8 + 7y) = 0
-48 + 24y + (8 * -1 + 7y * -1) = 0
-48 + 24y + (-8 + -7y) = 0

Reorder the terms:
-48 + -8 + 24y + -7y = 0

Combine like terms: -48 + -8 = -56
-56 + 24y + -7y = 0

Combine like terms: 24y + -7y = 17y
-56 + 17y = 0

Solving
-56 + 17y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + 17y = 0 + 56

Combine like terms: -56 + 56 = 0
0 + 17y = 0 + 56
17y = 0 + 56

Combine like terms: 0 + 56 = 56
17y = 56

Divide each side by '17'.
y = 3.294117647

Simplifying
y = 3.294117647

See similar equations:

| x^2-4x-50=0 | | (-2a^4b^4)(8a^3b^3)= | | 346=14+x | | 5-3x-9= | | 11x^2+5x+1=0 | | 4(5x+3)=20x | | 3+3+8(4-2k)+8(4-2k)=9 | | -12u=4u^2+9 | | 3(2U+9)=15 | | 4+x-6+3x=-2+6x | | 3t-5=32 | | 5/4= | | 4(4x-5)=2(8x+3) | | -b+8=1-8b+7 | | 217-39x=2100 | | 3x(2x+9)= | | 4+6s-1=9s+27-6s | | 8-y=2y-1 | | 9x+3=-32 | | 7x-2x=5x | | 3y^2=8y+3 | | 9-2(b+3)=4b | | r*r-10r+25=0 | | x+(x+5)=45 | | 5w^2+6=-17w | | -5-6p=2p+2 | | -7n+6=3(3n+10) | | 12.75x-15.35=3.124(2x+3) | | 2(5a-1)-4(-2a+3)= | | 21+9j+-10=-277 | | 1-6x=7+3x-8x | | y-(-75)=60 |

Equations solver categories